Analog IC test and product engineering curriculum for Malaysia microelectronics industry - Kamsani, Noor Ain; Mohd Sidek, Roslina; Yeo, C. W.; Gan, D.; Quek, C. T.; Krishnasamy, S.; Lee, Y. M.; Bolanos, M. A. (IEEE, 2014)
Production test is a significant driver of semiconductor manufacturing cost. Parallel with the advances of semiconductor fabrication, the need for a pool of talented product and test engineers is significantly increasing. This paper describes the academia-industries collaboration effort in developing an analogue electronic test and product engineering to boost-up technical competencies of electronic engineering graduates particularly in microelectronic major. The program has been successfully conducted at Universiti Putra Malaysia with strong support from Texas Instruments and Teradyne.